2005
DOI: 10.1021/bi051862l
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa C5-Mannuronan Epimerase:  Steady-State Kinetics and Characterization of the Product

Abstract: Alginate is a major constituent of mature biofilms produced by Pseudomonas aeruginosa. The penultimate step in the biosynthesis of alginate is the conversion of some β-D-mannuronate residues in the polymeric substrate polymannuronan to α-L-guluronate residues in a reaction catalyzed by C5-mannuronan epimerase. Specificity studies conducted with size-fractionated oligomannuronates revealed that the minimal substrate contained 9 monosaccharide residues. The maximum velocity of the reaction increased from 0.0018 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 27 publications
0
28
0
Order By: Relevance
“…A fixed time coupled assay for AlgG, modified from Jerga et al (31), was used to determine the activity of wild-type AlgG and its mutant variants. In the first step, 4 mg of poly(M) and 500 g of AlgG were mixed in 300 l of buffer C and incubated at 310 K for 40 h. AlgG and its mutant variants were subsequently inactivated by heating the mixture to 373 K for 10 min.…”
Section: Vinelandii))mentioning
confidence: 99%
See 2 more Smart Citations
“…A fixed time coupled assay for AlgG, modified from Jerga et al (31), was used to determine the activity of wild-type AlgG and its mutant variants. In the first step, 4 mg of poly(M) and 500 g of AlgG were mixed in 300 l of buffer C and incubated at 310 K for 40 h. AlgG and its mutant variants were subsequently inactivated by heating the mixture to 373 K for 10 min.…”
Section: Vinelandii))mentioning
confidence: 99%
“…Therefore, the other residues in the active site region of the D317A mutant have for clarity not been depicted. alginate epimerases use a similar reaction mechanism and because the AlgG epimerization reaction was found to be Ca 2ϩ -independent, then it is likely that AlgG uses an arginine to neutralize the negative charge of the uronic acid (31). Examination of the AlgG structure suggests that the most likely candidate for this role is Arg 345 (Fig.…”
Section: Algg Adopts a Right-handed Parallel ␤-Helixmentioning
confidence: 99%
See 1 more Smart Citation
“…The AlgG-type MEs are believed not to form G blocks, as alginates isolated from Pseudomonas species are devoid of such structural units. However, recently it was shown that Pseudomonas aeruginosa AlgG can form G blocks in vitro (30). An enzyme homologous to the Pseudomonas AlgG is also encoded in the A. vinelandii genome (48), but its epimerization pattern has not been experimentally determined, due to low in vitro activity.…”
mentioning
confidence: 99%
“…GDP-D-mannuronic acid is the activated sugar precursor for alginate polymerization in P. aeruginosa, which is a partially O-acetylated linear polymer of D-mannuronic acid and Lguluronic acid, linked via -1,4 glycosidic bonds (Shankar et al, 1995). In the case of the P. aeruginosa alginate, after polymerization, some D-mannuronic acid residues can be further converted to L-guluronic acid by the extracellular enzyme activity polymannuronic acid C-5-epimerase (Jerga et al, 2006). P. aeruginosa is able to cause severe and life-threatening infections in immunosuppressed patients, such as burn and cancer chemotherapy patients (Wagner and Iglewski, 2008), as well as in patients suffering from cystic fibrosis (CF).…”
Section: Gdp-d-mannuronic Acidmentioning
confidence: 99%